Cytokine responses to SARS-COV2 infection in mother-infant dyads: a systematic review and meta-analysis - Jain, Samhita; Allen, Isabel Elaine; Song, Dongli; Piao, Xianhua (Frontiers in Pediatrics, 2023)
The COVID-19 pandemic has affected a significant number of pregnant women worldwide, but studies on immune responses have presented conflicting results. This study aims to systematically review cytokine profiles in pregnant women with SARS-CoV-2 infection and their infants to evaluate immune responses and potential transplacental transfer of cytokines. Materials and Methods: A comprehensive search of 4 databases was conducted to identify relevant studies. Inclusion criteria included studies measuring individual cytokines in pregnant women and/or their neonates. Studies were evaluated for quality, and data were extracted for analysis. Meta-analyses were performed using the random-effects model. Results: Seventeen studies met the inclusion criteria, including data from 748 pregnant women and 287 infants. More than three of these studies evaluated data of 20 cytokines in maternal serum, and data of 10 cytokines was available from cord blood samples. Only the serum level of CXCL10 was significantly up-regulated in SARS-CoV-2 positive pregnant women (n=339) compared to SARS-CoV-2 negative pregnant women (n=409). Subset analysis of maternal samples (n=183) collected during the acute phase of COVID-19 infection showed elevated CXCL10 and IFN-γ. No significant differences in cytokine levels were found between cord blood samples collected from infants born to mothers with (n=97) and without (n=190) COVID-19 during gestation. Subset analysis of cord blood samples collected during the acute phase of maternal infection was limited by insufficient data. The heterogeneity among the studies was substantial.The findings suggest that maternal cytokines responses to SARS-CoV-2 infection during pregnancy are not significantly dysregulated, except for CXCL10 and IFN-γ during the acute phase of illness. No evidence of increased cytokine levels in cord blood samples was observed, although this could be impacted by the time period between initial maternal infection and cord blood collection. These results provide some reassurance to parents and healthcare providers but should be interpreted cautiously due to study variations and limitations.